Performance Assessment of Solar Air Heater Channel with Inclined Groove Turbulators - Koolnapadol, N.; Promvonge, P.; Khanoknaiyakarn, C.; Promthaisong, P.; Hoonpong, P.; Chaimanatsakun, A.; Gururatana, S.; Skullong, S. (My University, 2025)
An experimental investigation was carried out to explore the thermal performance and frictional loss features in a solar air heater (SAH) channel that was intentionally roughened on the absorber surface using multiple inclined groove turbulators. The working fluid, air, flows into the SAH channel, which has a consistent surface heat flux for Reynolds numbers (Re) varying between 5290 and 22,600 in the current research. Thermal characteristics at a single inclination angle (a = 45°) are investigated in this research by comparing the effects of three distinct relative groove frequencies (P/H=PR=0.8, 1.2 and 1.6) and groove depth ratios (D/H=DR=0.16, 0.24 and 0.32). The findings highlight that the employ of inclined grooves results in a noticeable rise in Nusselt number (Nu) from 1.24 to 2.82 times relative to the smooth absorber plate (smooth channel), as well as a 1.88 to 7.9 times increase in friction factor (f). The Nu and f show an increasing trend when Re increases, whereas the opposite pattern occurs as DR and PR increase. At PR = 0.8 and DR = 0.32, the inclined groove roughness has the largest thermal effectiveness factor (TEF) of around 1.64. The Nu and f correlations, which are functions of inclined groove features, have also been established.
Keywords: Heat transfer; Inclined groove; Solar air heater; Thermal performance